Improving Quality of Life on Cancer Patient by Implementation of Psychosexual Health Care - Yati Afiyati; Budi Keliat; Ida Ruwaida; Imami Nur Rachmawati; Nur Agustini (Universitas Airlangga, 2016)
Introduction: The contribution of nurses in improving the quality of life of patients with cancer has caused them to have needs of getting knowledge and skills to provide services on psychosexual health care. Training on psychosexual health care has been developed, implemented and given to oncology nurses in Indonesia in order to fulfill the needs so that the nurses are able to provide psychosexual health care to cancer survivors and their spouse.Method: The training utilized a method of pre- and post-test evaluation to identify outcomes including changes of evaluation scores of knowledge, belief, practice, and self-efficacy of trainees before and after receiving psychosexual health care training.Result: The training has been implemented on 46 oncology nurses in Indonesia so that they can have knowledge, practice, belief and self-efficacy in providing psychosexual health care to patients with cancer and their spouse. After training and mentorship had been provided, there were significant changes on knowledge, belief and self-efficacy in providing psychosexual health care services to patients with cancer and their spouse; however, there were no significant changes on practices.Discussion: The training has become a standard nursing care for cancer in Indonesia and has provided scientific evidences that nurses have contribution in improving quality of life of patients with cancer by providing a comprehensive nursing care through implementation of psychosexual health care in their daily nursing care for patients with cancer and their spouse.